Chemical attenuation of plasmodium in the liver modulates severe malaria disease progression - Lewis, Matthew; Lasitschka, Felix; Sattler, Julia M.; Heiß, Kirsten; Frischknecht, Friedrich; Müller, Ann-Kristin (The journal of immunology, 2015)
Cerebral malaria is one of the most severe complications of malaria disease, attributed to a complicated series of immune reactions in the host. The syndrome is marked by inflammatory immune responses, margination of leukocytes, and parasitized erythrocytes in cerebral vessels leading to breakdown of the blood-brain barrier. We show that chemical attenuation of the parasite at the very early, clinically silent liver stage suppresses parasite development, delays the time until parasites establish blood-stage infection, and provokes an altered host immune response, modifying immunopathogenesis and protecting from cerebral disease. The early response is proinflammatory and cell mediated, with increased T cell activation in the liver and spleen, and greater numbers of effector T cells, cytokine-secreting T cells, and proliferating, proinflammatory cytokine-producing T cells. Dendritic cell numbers, T cell activation, and infiltration of CD8+ T cells to the brain are decreased later in infection, possibly mediated by the anti-inflammatory cytokine IL-10. Strikingly, protection can be transferred to naive animals by adoptive transfer of lymphocytes from the spleen at very early times of infection. Our data suggest that a subpopulation belonging to CD8+ T cells as early as day 2 postinfection is responsible for protection. These data indicate that liver stage-directed early immune responses can moderate the overall downstream host immune response and modulate severe malaria outcome.